2005
DOI: 10.1063/1.1888044
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic silver nanoparticles fabricated by sputter deposition

Abstract: In this study a simple route to preparing photochromic silver nanoparticles in a TiO 2 matrix is presented, which is based upon sputtering and subsequent annealing. The formation of silver nanoparticles with sizes of some tens of nanometers is confirmed by x-ray diffraction and transmission electron microscopy. The inhomogeneously broadened particle-plasmon resonance of the nanoparticle ensemble leads to a broad optical-absorption band, whose spectral profile can be tuned by varying the silver load and the ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 36 publications
2
83
1
1
Order By: Relevance
“…It is worth noting that the process implemented by Zuo et al [ 26 ] using RF sputtering of a TiO 2 target gives rise to samples colored by the presence of Ag nanoparticles like in our MSM nanocomposite samples, whereas the samples obtained by Dahmen et al [ 24,25 ] …”
Section: Synthesis and Characterization Ofmentioning
confidence: 94%
See 1 more Smart Citation
“…It is worth noting that the process implemented by Zuo et al [ 26 ] using RF sputtering of a TiO 2 target gives rise to samples colored by the presence of Ag nanoparticles like in our MSM nanocomposite samples, whereas the samples obtained by Dahmen et al [ 24,25 ] …”
Section: Synthesis and Characterization Ofmentioning
confidence: 94%
“…[ 1 ] They have been suggested for a wide range of applications such as high-density multiwavelength optical data storage, [ 2 ] secure traceability, and rewritable color Jian et al deposited both sandwiched TiO 2 /Ag/TiO 2 and overcoated Ag/TiO 2 structures fi lms by dual-target helicon magnetron sputtering on quartz substrate at room temperature. [ 23 ] Dahmen et al [ 24,25 ] used DC sputtering of a Ag target and a Ti target in a Ar/O 2 atmosphere on glass, silicon and quartz substrates at room temperature with subsequent annealing at 300 °C. Zuo et al [ 26 ] used RF sputtering of a Ag target and a TiO 2 target on glass substrate at room temperature, followed by postgrowth annealing at 500 °C.…”
Section: Introductionmentioning
confidence: 99%
“…L'argent s'avère quant à lui être le métal noble le plus favorable à l'obtention de couleurs variées. Différents travaux rapportent un comportement photochromique avec des particules d'argent réduites au sein de matrices poreuses de TiO 2 de manière photocatalytique [5,[7][8][9][10], chimique [11,12] ou thermique [12,13] tout autant qu'avec des particules d'argent déposées par pulvérisation magnétron [14,15] ou par voie électrochimique [10]. On trouve des matrices poreuses préparées à partir de NPs de TiO 2 commerciales cristallisées dans la phase anatase [5,7,8,10] ou bien élaborées par voie sol-gel sous forme de films mésoporeux de TiO 2 amorphe [9,[11][12][13].…”
Section: Introductionunclassified
“…This is due to a spectrally selective photo-induced decrease in extinction. Two research groups have reported on fabrication of such structures photo/electro-catalytically [2][3][4][5] or by magnetron sputtering [6,7]. The properties of the material were investigated and mechanism of the observed photochromic changes suggested [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%